Physical, Chemical, and Organoleptic Characterization of Beetroot Leather (Beta vulgaris L.) with Additional CMC and Carrageenan - Pandeirot, Bellarose Novelia Kristina; Handoko, Yoga Aji (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2022)
The beetroot leather with CMC (Carboxyl Methyl Cellulose) or carrageenan as a binder resulted in beetroot leather with a dense clay texture and a good level of plasticity. Based on the benefits and content of beetroot and the addition of CMC and carrageenan, this research tries to characterize beetroot leather's physicochemical and organoleptic characteristics from various concentrations and types of thickening agents. This study was arranged in RBD (Randomized Block Design) with 6 treatments and 4 repetitions. CMC was expressed as factor X and carrageenan as factor Y with each concentration level (0.1%; 0.3%; 0.5%). Beetroot leather was tested physically, chemically, shelf life, and organoleptically. Physical tests include color and texture tests. Chemical tests include moisture, ash, antioxidant capacity, and total sugar. The data from observing physical and chemical properties were processed using the ANOVA (Analysis of Variance) method, further tested using DMRT (α=5%) and organoleptic using the Likert scale. The best treatment was found in X1Y1 (CMC 0.1%), which has good physicochemical content with a hardness level of 173.13g, deformation 2.07mm, dark purplish gray color, moisture content 15.72%, ash content 5.23%, total sugar 67.82%, and antioxidants 42.06%. Beetroot leather is easy to consume and has the best hardness level with a moisture content that is not too high, so it is not easily damaged. The organoleptic test showed that the respondents could not distinguish the five treatments and expressed their liking for all beetroot leather products.Keywords:  Beetroot leather, CMC, Carrageenan, Characterization, Organoleptic